The Zambezi River Basin : A Multi-Sector Investment Opportunities Analysis - State of the Basin - World Bank (World Bank, 2012)
The Zambezi River Basin (ZRB) is one of the most diverse and valuable natural resources in Africa. Its waters are critical to sustainable economic growth and poverty reduction in the region. The overall objective of the Zambezi River Multi-Sector Investment Opportunity Analysis (MSIOA) is to illustrate the benefits of cooperation among the riparian countries in the ZRB through a multi-sectoral economic evaluation of water resources development, management options and scenarios from both national and basin-wide perspectives. Better management and cooperative development of the Basin's water resources could significantly increase agricultural yields, hydropower outputs, and economic opportunities. Collaboration has the potential to increase the efficiency of water use, strengthen environmental sustainability, improve regulation of the demands made on natural resources, and enable greater mitigation of the impact of droughts and floods. Seen in this light, cooperative river basin development and management not only provide a mechanism for increasing the productivity and sustainability of the river system, but also provide a potential platform for accelerated regional economic growth, cooperation, and stability within the wider Southern Africa Development Community (SADC).